Effect of Computer-Based Laboratory Simulations (CBLS) in Acquisition of Scientific Inquiry Skills in electro_ chemistry in Secondary Schools in Bomet County - Kafu A. , Patrick; Chepkorir , Salome; Lusweti , Kituyi (African Journal of Education,Science and Technology (AJEST), 2022)
Computer technology has advanced to the point where it can significantly enable inquiry learning to be used at various levels, and offer new tools for representing the science nature in the classroom. It has been revealed that when using computer simulations in a situation where individuals are actively engaged can lead to content knowledge and conceptual change. The aim of this research was to examine the use of Computer-Based Laboratory Simulations (CBLs) in acquisition of inquiry skills in electro- chemistry in secondary chemistry instruction, Bomet County. This study adopted a Quasi-Experimental Research Design. SolomonFour Non-equivalent Groups Design was applied. Four secondary schools in Bomet County were purposively sampled on the basis of availability of computers. Three hundred and sixty-nine subjects took part in the investigation. The four schools were allocated to control and treatment groups by simple random sampling method. All groups of students were taught similar chemistry content (electro-chemistry). However, experimental groups used CBLs approach while the control groups used regular teaching methods (RTM) including teacher demonstrations and lecture. The control group II and experimental group I were pre-tested prior to the implementation of the CBLs treatment. After four weeks, all the groups (four) were post-tested using the Students’ Chemistry Achievement Test (SCAT) which was authenticated by education experts and pilot tested before using to validate its reliability. Data was analysed using ANCOVA, one-way ANOVA and t-test at a significant level of coefficient alpha (α) equal to 0.05. The findings indicated that computer-based laboratory simulations assisted students in acquisition of scientific inquiry skills (P<0.05). The study concluded that computer-based laboratory simulation had significant influence acquisition of inquiry skills in electro- chemistry. The study recommended teacher training programmes in universities be modified so as to include computer studies to empower teachers to be able to design CBLs programmes and use emergent technologies.